ANALISIS KEBUTUHAN MODAL KERJA PADA PDAM TIRTA MAYANG KOTA JAMBI PERIODE 2011-2015 - Arna Suryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The purpose of this study is as follows. Knowing enough working capital at PDAM Tirta Mayang Jambi 2011-2015 and analyzing the amount of working capital requirement at PDAM Tirta Mayang Jambi 2011-2015. In this study, the authors used secondary data. The data used are the financial statements of PDAM Tirta Mayang Jambi 2009-2013. Data collection methods used are library research. Data analysis method used is the analysis of qualitative and quantitative analysis. The analytical tool used is the analysis of working capital turnover, working capital needs analysis, and trend analysis of horizontal. Based on the analysis of the table shows that the working capital needs analysis on PDAM Tirta Mayang Jambi City has fluctuated over the last 5 years. In 2015 the working capital requirements analysis biggest by the number           Rp 21,042,794,4. In 2011 the working capital needs analysis is the smallest with a number Rp 10,115,197. With total working capital needs analysis Rp14,802,778.54 and with average Rp 55,230,723. Keyword : capital, company